Konflik Fungsional dalam Kumpulan Cerpen Rubrik Sastra Kompas.ID 2024 dan Pemanfaatannya Sebagai Alternatif Materi Pembelajaran Sastra di SMA Kelas XI - Sinta Nuriyah Zaeni (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examines functional conflict in a collection of short stories from the literary section of Kompas.id 2024 using a sociology of literature approach based on Lewis A. Coser's functional conflict theory. This research aims to describe the forms of functional conflict, the factors causing conflict, the positive functions of conflict, and the utilization of the research findings as an alternative literary learning material for eleventh grade senior high school students under the Kurikulum Merdeka (Independent Curriculum). This research employs a qualitative method with documentation as the data collection technique and Miles and Huberman's interactive model as the data analysis technique, encompassing data reduction, data display, and conclusion drawing and verification. The primary data sources consist of five short stories from the literary section of Kompas.id published 2024, namely Kota Penyambung Asa, Raja dan Batu Langit, Kado dari Guru Honor, Rumah Tepi Kali, and Ngaben Sederhana. The findings reveal that functional conflict in the five short stories is divided into two forms, namely realistic conflict found in four forms and non-realistic conflict found in two forms. The factors causing conflict originate from individual differences, differences in sosial class and culture, differences in interests, and sosial change. The positive functions of conflict are found in five forms based on Coser's propositions, namely strengthening internal group solidarity, affirming group boundaries and identity, promoting consensus within the group, correcting deviance, and opening space for individual awareness. The research findings can be utilized as an alternative literary learning material for eleventh grade senior high school students under the kurikulum merdeka (Independent Curriculum) phase F in the reading and writing element. This study concludes that conflict in literary works is not always destructive but can function positively as a sosial mechanism that strengthens interpersonal relationships among characters and reflects the sosial dynamics of Indonesian society.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Short Story Collection; Sociology of Literature; Lewis A. Coser